E-Banking Complexities and the Perpetual Effect on Customer Satisfaction in Nepalese Commercial Banks - Purbey, Shweta; Shakya, Sarina; Nepal, Sushmita; Bhurtel, Sushila; Adhikari, Sudarshan; Khadka , Swosti; Pradhan, Sumit (Nepalese Journal of Economics, 2025)
This study examines the e-banking complexities and the perpetual effect on customer satisfaction in Nepalese commercial banks. Customer satisfaction is the selected dependent variable. The selected independent variables are authentication difficulties, trust, privacy concern, reliability, technical errors and personal interaction. The primary source of data is used to assess the opinions of the respondents regarding e-banking complexities and level of satisfaction in Nepalese commercial banks. The study is based on primary data of 113 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of e-banking complexities on customer satisfaction in Nepalese commercial banks. The study showed that trust has a positive impact on customer satisfaction. It indicates that higher the trust of the customer on e-banking, higher would be the customer satisfaction. Likewise, reliability has a positive impact on customer satisfaction. It indicates that higher reliability on e-banking leads to increase in the level of customer satisfaction in Nepalese commercial banks. The result also revealed that authentication difficulties has a negative impact on customer satisfaction. It implies that more authentication difficulties leads to decrease in the level of customer satisfaction in Nepalese commercial banks. Similarly, privacy concern has a negative impact on customer satisfaction. It implies that higher privacy concern and risk leads to decrease in customer satisfaction to use digital banking services. Likewise, personal interaction has a positive impact on customer satisfaction. It states that increase in personal interaction leads to increase in customer satisfaction in Nepalese commercial banks. Similarly, technical error has a negative impact on customer satisfaction. It shows that high technical error leads to decrease in the level of customer satisfaction in Nepalese commercial banks.